2019
DOI: 10.33899/ijvs.2019.162965
|View full text |Cite
|
Sign up to set email alerts
|

Nad1 gene analysis of Echinococcus granulosus from sheep in Aqrah city, Iraq

Abstract: Echinococcus granulosus (E. granulosus) is a dog tapeworm cestoda; it is larval stage responsible to cystic echinococcosis, one of the most common and dangerous worldwide zoonotic parasitic disease. The aim of this study was the molecular identification of the local strain of E. granulosus isolated from sheep liver slaughtered in the principal abattoir of Aqrah city, Northern of Iraq during Jun-Nov. 2017. In this study, 37 sheep liver infected by E. granulosus, 12 of high DNA purity fertile (have protoscolices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…These finding suggests that the sheep-dog cycle occur in this region. However, genotyping of sheep hydatid cysts using sequencing with cox1 gene, G1 is described as predominant genotype in various countries such as Peru (18), Egypt (19) China, Turkey, Italy and Tunisia that are consistent with this study (20)(21)(22) and with highly remarkable corresponding to north African and Mediterranean countries isolates (23). Genotype of E. granulosus, mitochondrial genes are much better than other genome sources for E. granulosus genotyping.…”
Section: Discussionsupporting
confidence: 84%
“…These finding suggests that the sheep-dog cycle occur in this region. However, genotyping of sheep hydatid cysts using sequencing with cox1 gene, G1 is described as predominant genotype in various countries such as Peru (18), Egypt (19) China, Turkey, Italy and Tunisia that are consistent with this study (20)(21)(22) and with highly remarkable corresponding to north African and Mediterranean countries isolates (23). Genotype of E. granulosus, mitochondrial genes are much better than other genome sources for E. granulosus genotyping.…”
Section: Discussionsupporting
confidence: 84%
“…Various diagnostic approaches were employed to differentiate pathogenic parasites of human and animals, including Fasciola, but at least until now, molecular protocols are the best, the precise, and fully future (15)(16)(17). This study, as the knowledge of the authors, is the first in Iraq that utilized an 18S rRNA gene of F. gigantica in the confirmed diagnosis and differentiation with global isolates which documented in NCBI and GenBank.…”
Section: Discussionmentioning
confidence: 89%
“…The results demonstrated in this investigation agree with Iraqi isolates. Hamoo and Abdulraheem (2019) showed that the local isolate is G1 genotype (sheep strain), and the phylogenetic results were compatible with North Africa and the Middle East isolates as 95% and 96%. Fadhil & A'aiz (2016) reported three strains of the E.granulosus parasite, sheep strain (G1) 40%, buffalo strain (G3) 48% and camel strain (G6) 12%.…”
Section: Discussionmentioning
confidence: 52%